GAMBARAN PENGETAHUAN WANITA PEKERJA SEKS (WPS) TENTANG PENYAKIT HIV/AIDS DILOKALISASI BUKIT MARAJA DESA MARIHAT BUKIT KECAMATAN GUNUNG MALELA KABUPATEN SIMALUNGUN 2014 - Indra Wilson Purba; Kintoko Rochadi; Alam Bakti Keloko (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACTHuman Immuno defiency Virus ( HIV ) is a virus that attacks the human immune system and weakens the body's ability to fight disease came. The discovery of cases of HIV / AIDS on Women Sex Workers (WSW) in Localization Bukit Maraja Desa Marihat Bukit Kecamatan Gunung Malela Kabupaten Simalungun may be influenced by the level of knowledge of Women Sex Workers (WSW) on sexually transmitted diseases ( STDS). This research aims to describe the knowledge Women Sex Workers ( WSW ) of the Human Immuno Deficiency Virus disease / Acquired Immuno Deficiency Syndrome ( HIV / AIDS ) in Bukit Maraja Desa Marihat Bukit Kecamatan Gunung Malela Kabupaten Simalungun in the year of 2014 . This research was a descriptive study with cross design sectional . Research was all Women Sex Workers ( WSW ) in Localization Bukit Maraja Desa Marihat Bukit Kecamatan Gunung Malela Kabupaten Simalungun In the year of 2014 was 135 people research of this study was 56 people, for sampling method using by simple random sampling . The data of Primary was performed by direct interviews with patients using questionnaires to Women Sex Workers ( WSW ) and secondary data obtained from Bukit Maraja Health Center .The results of this research showed that the respondents' knowledge based on good category of either the 42 people ( 75 % ) level of knowledge sufficient was 13 people ( 23.2 % ) and level of poor knowledge was 1 people ( 1.8 % ) . In generally , the respondents' attitudes based on high category was 54 people ( 96.4 % ) and then followed by the category of less attitude was 2 people ( 3.6 % ) . And also, category of respondents' attitudes was in good category by 49 people ( 87.5 % ) and then followed by suffient behavior of 7 people ( 12.5 % ) . Based on respondents resources on HIV / AIDS at the most sourced from friends that amounted all of people ( 32.1 % ) . Suggested to the health department can utilize methods that will take advantage of the peer educater WPS to be able to provide information about HIV / AIDS to the other people .Keywords : Knowledge , women sex workers , HIV / AIDS.